Study of the Dielectric Properties Ceramics Specimens Prepared from Alumina and MgO - Maki, S. A.; Al-Dahan, Z. T.; Abd Al-Hassan, Sh. K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
A study carried out on ceramic material made at (a-Al2O3) doped with MgO (0.5 , 0.3 , 0.2,0.1)%,with particle size at 63mm. A Hydraulic press of 5kn at diameter of 2cm.A nnalelling at 1500Co and 6 hrs still to see the effect on the changes of the dielectric material. With frequency range at (1K – 1M) Hz. And the result show that at percentage of 0.5% of MgO, the real dielectric material decreased with the increased frequency